The Influence of the Independent Learning Program Policy on the Development of Soft Skills of Office Administration Education Students - Andi Sabina Ainun Nisa; Sitti Hardiyanti Arhas; Muh Nasrullah (International Journal of Administration and Education (IJAE), 2026)
The Ministry of Education, Culture, Research, and Technology of the Republic of Indonesia strives to increase the relevance of higher education to the needs of the world of work through the implementation of the independent campus learning program policy.  The objectives of this study are as follows: (1) explaining the policy of the free campus learning program and the development of students' soft skills; (2) to measure how much the policy affects the development of students' soft skills at the Faculty of Office Administration FIS-H UNM. To achieve this goal, a quantitative research method, specifically an associative type of research, is used. To achieve the research objectives, data was collected through observation, questionnaires, and documentation. The population in this study amounted to 153 students, with a total of 110 students taken as samples using the propotione stratified random sampling technique. The data obtained from the results of the research were processed using descriptive analysis techniques and inferential analysis techniques to determine the influence of the independent learning program policy on the development of soft skills of students of Office Administration Education FIS-H UNM. The results of the research in chapter IV show that (1) the policy of the independent learning program affects the development of soft skills of students of Office Administration Education FIS-H UNM. (2) The correlation coefficient was obtained of 0.652 which shows that the relationship between the policy of the independent learning program of the independent campus and the development of soft skills is strong. The determination coefficient was obtained as 0.424 meaning 42.4%, which shows that the influence of the independent campus learning program policy on the development of soft skills of FIS-H UNM Office Administration Education students is 42.4% (assuming that other factors are constant).